Mechanism of Effect of Prostaglandin E(1) on Renal Water Excretion - Berl, T. (1973)
The present study examined the effect of prostaglandin E(1) (PGE(1)) on renal water excretion in the anesthetized dog. Renal perfusion pressure was kept constant by adjustment of a suprarenal aortic clamp. In seven experiments the intravenous administration of PGE(1) (7 μg/min) significantly increased urinary osmolality from 76 to 381 mosmol (P < 0.001) and decreased free water clearance from 2.2 to - 0.02 ml/min (P < 0.001). These effects promptly were reversed with cessation of the infusion. This antidiuretic effect occurred both in innervated and denervated kidneys and was not associated with changes in glomerular filtration rate, renal vascular resistance, or solute excretion rate. In 10 experiments in hypophysectomized dogs no effect of intravenous PGE(1) on free water clearance and urinary osmolality was observed. The intrarenal administration of PGE(1) (1 μg/min) to six water-loaded and two hypophysectomized dogs caused no systemic vascular changes and increased rather than decreased free water clearance (2.83 to 4.08 ml/min, P < 0.001). No significant change in urinary osmolality occurred. Glomerular filtration rate was not altered by the intrarenal infusion, but reversible changes in solute excretion rate and renal vascular resistance occurred. These results thus indicate that the antidiuresis associated with intravenous PGE(1) is mediated primarily by the release of vasopressin rather than alterations in renal hemodynamics or solute excretion. The diuretic effect of intrarenal PGE(1) occurs in the absence of vasopressin and is most likely mediated primarily by increased distal delivery of tubular fluid to the diluting segment of the nephron rather than changes in water permeability of the renal tubular epithelium.